Heat exchanger for solar collector - Lagunesvary, Ganesan (2013)
The objective of this study is to design and simulate an optimum heat exchanger for evacuated tube solar collector. The simulation was carried out in ANSYS FLUENT 14.0 with two different tube designs, spring and S-Shape. Four materials was analysed in this study, copper, aluminium, steel and brass. Both tube designs are varied by three different sizes and four shapes, circular, ellipse, square and hexagon. There are four flow rates are considered in the study, 1kg/s, 0.5kg/s, 0.25kg/s and 0.01kg/s. Based on the study, copper 61.25% effective compare to aluminium and followed by steel and brass. In the overall, spring design performs better than S-Shape design and ellipse shape tube in leading. At the flow rate of 1kg/s, large size ellipse-spring tube design provide higher performance with rate of heat transfer 109192.02W. At flow rate of 0.5kg/s and 0.25kg/s medium size ellipse-spring tube design performs better than the others. While at the flow rate of 0.01kg/s, small size ellipse-S-Shape design is chosen.